2015
DOI: 10.1080/02772248.2015.1068316
|View full text |Cite
|
Sign up to set email alerts
|

The physiological impact of bisphenol A on the developmental and reproductive processes ofSesamia nonagrioides(Lepidoptera: Noctuidae) under LD and SD photoperiods

Abstract: In this study we examined the physiological impact of Bisphenol A on the developmental and reproductive processes of Sesamia nonagrioides (Lepidoptera: Noctuidae) under 16L:8D (long day, LD) and 10L:14D (short day, SD) photoperiods. Larvae were continuously exposed to different concentrations of BPA (1, 10 and 100 μg/L) applied in their artificial diets, under LD and SD conditions. During LD photoperiod increased pupal weights were observed in insects grown in culture media with the higher dose of 100 μg/L BPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Embryonic exposures to BPA and BPA analogs can directly result in long-term disease and acute and chronic health impacts related to reproduction, development, and somatic growth across species; therefore, understanding the developmental effects of these environmental chemicals is critical ( Chianese et al, 2018 , Kitamura et al, 2005 , Vandenberg et al, 2007 , Vandenberg et al, 2019 ). Many studies have reported that BPA has developmental effects in vivo at various concentrations across many species from invertebrates, to tunicates, amphibians, fish, chicken, mice, and monkeys ( Brannick et al, 2012 , Crump et al, 2016 , Huang et al, 2011 , Hunt et al, 2012 , Iwamuro et al, 2003 , Kontogiannatos et al, 2015 , Matsushima et al, 2013 , Mentor et al, 2020 , Moreman et al, 2017 , Qui et al, 2016 , Saito et al, 2012 , Tharp et al, 2012 , Tomohiro et al, 2003 , Wolkowicz et al, 2014 ). We and others have found that BPA and certain BPA analogs cause severe developmental defects in early Xenopus and zebrafish embryos, specifically inducing severe body axis and scoliosis-type spinal cord defects, decreased growth and body length and size, craniofacial malformations, eye dysplasia and pigmentation defects, loss of body pigmentation, gut and heart defects and edema, and high mortality rates ( Arancio et al, 2018 , Arancio et al, 2019 , Baba et al, 2009 , Huang et al, 2016 , Moreman et al, 2017 , Pinto et al, 2019 , Tomohiro et al, 2003 , Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic exposures to BPA and BPA analogs can directly result in long-term disease and acute and chronic health impacts related to reproduction, development, and somatic growth across species; therefore, understanding the developmental effects of these environmental chemicals is critical ( Chianese et al, 2018 , Kitamura et al, 2005 , Vandenberg et al, 2007 , Vandenberg et al, 2019 ). Many studies have reported that BPA has developmental effects in vivo at various concentrations across many species from invertebrates, to tunicates, amphibians, fish, chicken, mice, and monkeys ( Brannick et al, 2012 , Crump et al, 2016 , Huang et al, 2011 , Hunt et al, 2012 , Iwamuro et al, 2003 , Kontogiannatos et al, 2015 , Matsushima et al, 2013 , Mentor et al, 2020 , Moreman et al, 2017 , Qui et al, 2016 , Saito et al, 2012 , Tharp et al, 2012 , Tomohiro et al, 2003 , Wolkowicz et al, 2014 ). We and others have found that BPA and certain BPA analogs cause severe developmental defects in early Xenopus and zebrafish embryos, specifically inducing severe body axis and scoliosis-type spinal cord defects, decreased growth and body length and size, craniofacial malformations, eye dysplasia and pigmentation defects, loss of body pigmentation, gut and heart defects and edema, and high mortality rates ( Arancio et al, 2018 , Arancio et al, 2019 , Baba et al, 2009 , Huang et al, 2016 , Moreman et al, 2017 , Pinto et al, 2019 , Tomohiro et al, 2003 , Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%